Age and growth of two sharpnose shark species (Rhizoprionodon lalandii and R. porosus) in subtropical waters of the south-western Atlantic - Corsso, Jessica T.; Gadig, Otto B. F. [UNESP]; Caltabellotta, Fabio P.; Barreto, Rodrigo; Motta, Fabio S. (Csiro Publishing, 2020)
The age and growth of subtropical populations of the Brazilian and Caribbean sharpnose sharks (Rhizoprionodon lalandiiandR. porosusrespectively) were determined by combining direct and indirect ageing methods, maximising the use of available information. Using vertebrae ageing forR. lalandii, the theoretical maximum length L-infinity and growth coefficientkwere 661.9 mm and 1.14 year(-1)for males and 751.7 mm and 0.59 year(-1)for females. Vertebrae were not sampled forR. porosus. Values ofL(infinity)andkfrom electronic length-frequency analyses (ELEFAN) were 762 mm and 0.71 year(-1)for maleR. lalandii, 791 mm and 0.67 year(-1) for femaleR. lalandii, 1040 mm and 0.41 year(-1)for maleR. porosusand 1165 mm and 0.31 year(-1) for female R. porosus. Growth during the first year of life in relation to birth size was 80.3% for R. lalandiiand 55% forR. porosus. Both species exhibit rapid growth, primarily in the first year of life. The growth estimates forR. lalandii and R. porosus are even faster than those reported in previous studies from tropical populations.
Keywords: elasmobranch; fishery management; length-frequency ageing; life history; vertebrae ageing